Dark data management among Malaysian small and medium enterprises: a grounded theory analysis / Ahmad Fuzi Md Ajis - Md Ajis, Ahmad Fuzi (2023)
Dark data immerse within an organizational repository either virtually or physically, yet its significant value is not fully appraised by the owner. Some of the consequences of dark data include the widespread use of duplicated and distributed content without explicit oversight, which weakens security. The sheer volume of dark data impacts the costs of searching and producing appropriate information and imposes a wasted storage cost in operating budgets. The majority of the literature highlighted dark data research from the perspective of academic research institutions and large business firms, and none was found pertaining to Small and Medium Enterprises (SMEs). Therefore, grounded theory research was conducted to investigate the dark data phenomenon towards SMEs in Malaysia. The primary goal of the research is to investigate the dark data phenomenon in Malaysian small and medium enterprises to determine why and how dark data is managed by SMEs. The theoretical Sampling method was employed in the study, which involved 18 SMEs from all business sectors and business sizes in Malaysia.